2014
DOI: 10.4103/2277-9175.139538
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and total antioxidant capacity in handball players

Abstract: Background:Exercise training increases oxygen consumption, which was associated with the high generation of reactive oxygen species and markers of lipid peroxidation in the blood. The aim of this study was to assess the responses of total antioxidant capacity (TAC), biomarker of oxidative stress and erythrocyte, leukocyte and hematocrit (Hct) levels in plasma in athlete girls (handball players) and non-athlete girls.Materials and Methods:We evaluated two groups, which known as athlete and non-athlete women and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…The results are consistent with the findings of Mehregan et al (2023) [24]. However, it is not consistent with the findings of Koubaa et al (2023) and Sharifi et al (2014) [25,26]. Mehregan et al (2023) investigated the effect of four weeks of high-intensity interval training compared with aerobic training on serum ceruloplasmin and MDA levels in elite female handball players.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The results are consistent with the findings of Mehregan et al (2023) [24]. However, it is not consistent with the findings of Koubaa et al (2023) and Sharifi et al (2014) [25,26]. Mehregan et al (2023) investigated the effect of four weeks of high-intensity interval training compared with aerobic training on serum ceruloplasmin and MDA levels in elite female handball players.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, Koubaa et al (2023) investigating the effect of three warm-up periods on post-exercise oxidative stress in 14 amateur handball players, concluded that the concentration of most oxidative stress indices, such as glutathione peroxidase, superoxide dismutase, glutathione reductase, and thiobarbituric acid reactive substances were significantly increased [25]. Sharifi et al (2014) reported that six months of handball training, three sessions per week in 30 students divided into two groups of athletes and nonathletes, resulted in a decrease in the levels of MDA in athletes compared to non-athletes [26]. Antioxidants can act by different mechanisms, such as removal of oxygen or local oxygen concentration, extraction of catalytic metal ions such as Cu 2+ , Fe 2+ , ROS, such as superoxide and hydrogen peroxide, and interruption of chain reactions.…”
Section: Discussionmentioning
confidence: 99%
“…This overall variation in Hgb and Hct might be due to differences in the level of athletes, dose and duration of hypoxia exposure, plasma volume level, training frequency and intensity, age of study subjects, and nutrition. Physical training and duration of exercise have major importance in the adaptation of the blood cell system [ 58 , 59 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercise or chronic anaerobic training can enhance endogenous antioxidant defence mechanisms, reducing oxidative damage [ 129 , 130 ]. However, it has been suggested that rigorous training or prolonged competition periods may increase OS [ 131 ]. This is because ROS release can dysregulate the inflammatory and neuroendocrine systems, which may exceed the capacity of the antioxidant system to protect against damage [ 132 ].…”
Section: Non-communicable Diseases and Environmental Impact On Mitoch...mentioning
confidence: 99%